Equine neorickettsiosis: A global perspective of the natural habitat of the bacteria and clinical disease - Luis G. Arroyo; Alexandre S. Borges; John D. Baird; Brian D. Perry; Yasuko Rikihisa; Stephen E. Greiman (Veterinary Microbiology, 2026)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

The suppression of lower leg electromyography when walking in textured foot orthoses - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

Capitalizing on skin in orthotics design: the effects of texture on plantar intrinsic foot muscles during locomotion - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

The topographical attenuation of cutaneous input is modulated at the ankle joint during gait - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

The effect of texture under distinct regions of the foot sole on human locomotion - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

Determining the influence of environmental and patient specific factors on the polymicrobial communities of the cystic fibrosis airway - Andrew Nelson; Audrey Perry; John D. Perry; Stephen J. Bourke; Stephen P. Cummings; Anthony De Soyza (Antonie van Leeuwenhoek, 2013)

The controls on phosphorus availability in a Boreal lake ecosystem since deglaciation - Stephen A. Norton; Randall H. Perry; Jasmine E. Saros; George L. Jacobson; Ivan J. Fernandez; Jiří Kopáček; Tiffany A. Wilson; Michael D. SanClements (Journal of Paleolimnology, 2011)

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)